The suitability of active inductors for a wide range of CMOS implementations - Kızmaz, Muhammed Mustafa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Integrated circuits (ICs) form the heart of today's technology thanks to their prominent features such as minimal size, reduced cost, high reliability, and low power consumption. Then, inductors have found a wide range of uses in modern IC implementations. These application areas can be exemplified by impedance matching, bandwidth enhancement, gain boosting, frequency selection, phase shifters, and LC oscillators. The frequently preferred method for the required inductances is using CMOS spiral inductors. However, spiral inductors have significant shortcomings that limit their use in CMOS realization. For example, spiral inductors consume a large chip area, and it is impossible to tune their inductance values. Moreover, these inductors have low quality factors (Q) and low self-resonant frequencies. Due to the drawbacks of spiral inductors, researchers have been looking for alternatives. One of these approaches is active inductors (AIs), which use active circuit components to synthesize required inductance. Numerous AI topologies have been presented in the literature. Each architecture may be selected depending on the inductance needs of the application. Thus, AIs have a broad variety of applications in CMOS implementations due to their diversity of topologies. This thesis demonstrates that employing AIs is feasible for a range of CMOS implementations. Its feasibility is proven by designing an AI-based wide-tunable LC voltage- controlled oscillator (LC-VCO), a lattice-based allpass filter, and an autonomous chaotic oscillator.
Keywords: Integrated circuits.